Smooth sailing: market integration, agglomeration, and productivity growth in interwar Brazil - Badia-Miró, Marc; Carreras-Marín, Anna; Huberman, Michael (European Review of Economic History, 2023)
Leveraging an original dataset on coastal shipping and invoking a new economic geography framework, we study the effects of domestic and international trade costs on industrial concentration and productivity growth in interwar Brazil. In the great wave of globalization before 1914, international trade costs were low and domestic costs high. Economic activity was dispersed along the coastline. The interwar period saw a reversal: international costs surged and domestic costs declined. Economic activity was increasingly concentrated in São Paulo. Agglomeration economies enabled productivity growth in the 1930s, mostly in durable and capital goods.